Ritual Matters: Changing Ontologies, Values, and Ecological Conscience Formation - Davy, Barbara Jane; Quilley, Stephen (Journal for the Study of Religion, Nature & Culture, 2018)
Karl Polanyi (1944, 1968) argued that the 'disembedding' of the economy from society entailed a curtailment of social constraints on economic transactions. This disembedding coincided with what Max Weber (1946) called disenchantment, and the erosion of cognitive-experiential reciprocity between humans and nature. Following Lynn White Jr. (1967), many scholars of religion and ecology have argued that losing the sense of divinity immanent in the world caused the modern devaluation of nature. But the loss of ritual practices is key to this. Integrating Roy Rappaport's (1968, 1979, 1999) understanding of the regulative ecological functions of ritual with a processual understanding of ontology following Norbert Elias (1939, 1978, 1989) suggests that reviving ritual gifting practices may be a vehicle for ecological conscience formation and the social-ecological transformation of modern society. Removing the rituals surrounding the giving of gifts removed crucial informal governance structures from pre-modern cultures, resulting in a general collapse of meaning structures in modern market societies, producing a pervasive individualized ontology and what Elias (1991) called 'the society of individuals'. A revival of ritual gifting practices that re-enchant human relations with other than human persons, such as found in what Graham Harvey (2006, 2016) has called 'the new animism', may revive relational ontology and shift modern society toward a more sustainable path by re-embedding the economy in society.
Keywords: POLANYI, Karl, 1886-1964; animism; ecological conscience formation; ecology - religious aspects; environmental behaviour; gift economy; informal governance; new animism; ontology; relational ontology; religion and ecology; ritual; systems theory; systems thinking

The Significance of Polanyi's Contribution: An Interpretation of the Neoliberalization and Commodification of Nature - Iannuzzi, Giulia (Janus.Net: e-Journal of International Relations, 2018)
Polanyi's analysis and contributions have been brought back into discussion due to the rapid emergence of market-based instruments designed to tackle environmental degradation. Polanyi is a crucial reference in current debates on globalization and international political economy. This article seeks to explore and discuss how his perspective, and the founding concepts of his work, can help us to interpret the current process of the neoliberalization and commodification of nature.
Keywords: commodification; commodification of nature; environment; globalization; international relations; neoliberalism

Unpacking the objectives and assumptions underpinning European aquaculture - Ertör, Irmak; Ortega-Cerdà, Miquel (Environmental Politics, 2017)
Increasing demand for seafood and the lack of growth of capture fisheries have boosted aquaculture growth worldwide. However, European aquaculture has been stagnating over the past decade, and European public authorities have been developing policies and strategies in efforts to reverse this. Aquaculture discourses in the European Union, based on 34 policy, planning, and strategy documents, are examined and a discourse analysis conducted following Bacchi's WPR (What is the Problem Represented to be?) approach. How the problems in these discourses are represented, the tensions among main objectives, and the implicit assumptions are unveiled, and discussed employing a Polanyian theoretical framework. Taking these assumptions for granted leads to a disembedded understanding of aquaculture, and facilitates the privatization of aquatic space and resources. The analysis contributes to the literature establishing the link between the expansion of aquaculture and the enclosure of aquatic resources and enriches environmental and political debates on European aquaculture.
Keywords: Europe; European Union law; aquaculture; aquatic resources; discourse analysis; enclosures; environmental politics; fisheries; fishery policy; government policy; privatization

CSR as a legitimatizing tool in carbon market: Evidence from Latin America’s Clean Development Mechanism - Benites-Lazaro, L.l.; Mello-Théry, N.A. (Journal of Cleaner Production, 2017)
Clean Development Mechanism (CDM) has incorporated sustainable development as one of their objectives. This objective gives companies an increasing motivation to contribute to sustainable development through their corporate social responsibility (CSR). However, perceived profitability of companies with carbon commodification were negatively associated with CDM projects. This paper aims to identify CSR activities in CDM in three Latin American countries, namely, Brazil, Mexico, and Peru and understand the drivers behind of these CSR initiatives. The study is based on the evaluation of 593 projects registered and Polanyi’s theory. We identified some CSR activities corresponding to the social, environmental and economic indicators in the three countries. This is not to say that all CDM developers are acting in a socially responsible manner. Certain CSR activities in most of the cases were implemented as a way to legitimize and as a means to achieve social acceptance.
Keywords: CSR; Latin America; carbon dioxide mitigation; clean development mechanism; corporate legitimacy; corporate social responsibility; double movement; double-movement; economic aspects; embeddedness; emission control; social acceptance; social responsibility of business

Moving targets: Carbon pricing, energy markets, and social movements in Australia - Pearse, Rebecca (Environmental Politics, 2016)
Reporting on the origins and directions of social movement strategy on climate and energy issues in the last decade, the shifts in ‘climate movement’ practice are discussed using a neo-Polanyian account of the political economy of climate change combined with sociological analysis of the strategic decisions campaigners reported making. Since the mid-2000s, Australia’s climate movement has been engaged in three concurrent arenas of political contestation. The longest-standing arena of movement activity has been negotiations over climate policy. More recently, activists and communities are engaged in a struggle over the expansion of fossil fuels. A third contest has been waged over the present and future position of renewable energy technologies in Australia’s electricity market. In the wake of climate policy failure, energy campaigns have been deepened, and it seems that a broader energy justice agenda is being forged. New strategic dilemmas are visible in the field.
Keywords: Australia; carbon pricing; climate policy; climatic changes; economics; energy industries; energy markets; fossil fuels; renewable energy sources; social movements

The Copenhagen Turn in Global Climate Governance and the Contentious History of Differentiation in International Law - McGee, Jeffrey; Steffek, Jens (Journal of Environmental Law, 2016)
The 2009 Copenhagen Accord marked a significant shift in global climate governance which has been substantially adopted in the 2015 Paris Agreement. At Copenhagen, binding targets for states to reduce emissions were replaced by voluntary pledges. We argue that the Polanyian 'double movement' offers a useful lens to understand the Copenhagen shift in global climate governance as part of ongoing contestation in the international law system between principles of economic liberalisation and redistributive intervention. In the second half of the 20th century, redistributive design of international legal institutions became evident in a number of issue areas including trade law, oceans law and the seminal climate treaties. However, there has been ongoing US lead opposition to 'redistributive multilateralism' (RM), particularly over the last decade of climate negotiations. The Copenhagen model of voluntary pledges, therefore, needs to be viewed as an outcome of this opposition to RM and a related weakening of differentiation in international environmental law.
Keywords: Copenhagen; Copenhagen Accord; UNFCCC; climate change; differentiation of duties; environmental justice; environmental law; international cooperation; international law; political economy; regime design

Economy, Society and Earth in Polanyian and Wild Law Perspectives on Environmental Regulation: To Perform a Double or Triple Movement? - Pontin, Ben (Journal of Environmental Law, 2016)
Keywords: BURDON, Peter D.; HAINES, Fiona; LANGE, Bettina; MALONEY, Michelle; Regulatory Transformations: Rethinking Economy-Society Interactions (Book); THOMAS, Dania; Wild Law: In Practice (Book); book review; double movement; environmental law; nonfiction; triple movement

Indigenous Development and the Cultural Captivity of Entrepreneurship - Peredo, Ana María; McLean, Murdith (Business & Society, 2013)
This article argues that thinking about entrepreneurship as a potential instrument for relief from endemic poverty and disadvantage, especially among the Indigenous, has all too often been captive to a concept of entrepreneurship that is built out of constrained economic and cultural assumptions. The authors develop this argument from a critical discussion of contributions by Karl Polanyi and Robert Heilbroner. The result is that approaches to venture have been encouraged that are sometimes a poor fit for the circumstances of those they are meant to benefit, and other forms that could have considerable promise have gone unexplored. This article outlines some features of Indigenous culture and build on the analysis of David Harper to construct an improved notion of entrepreneurship that allows for these distinctive features. The article concludes that research and policy making concerning entrepreneurship as an instrument of development among the Indigenous need to be undertaken with this reconstructed understanding of entrepreneurship that is a better fit for the realities of Indigenous culture.
Keywords: HEILBRONER, Robert; Indigenous development; Indigenous peoples; POLANYI, Karl, 1886-1964; cultural diversity; entrepreneurship; entrepreneurship and culture; poverty

Housing Projects for Low-Income Groups and Modes of Economic Integration: A Comparative Study in Greater Cairo - Abouelmagd, Doaa; Kesteloot, Christian; Corijn, Eric (Tijdschrift voor Economische en Sociale Geografie (Journal of Economic & Social Geography), 2013)
The housing of low-income groups in Greater Cairo has always been difficult. However, the general shortage in housing supply is contrasting with the low occupancy rate of newly constructed public housing units. In contrast, despite their bad living conditions, informal settlements have a high occupancy rate. In order to analyse the reasons behind this contradiction, the paper compares four neighbourhoods ranging from formal and semi-informal to informal housing production and including one rehabilitation project. The livelihood conditions in each settlement are unravelled with the concept of modes of economic integration from Polanyi. For this purpose, semi-structured interviews were conducted and analysed with correspondence analysis. The findings indicate a preference among low-income groups for informal settlements because of three reasons: the advantages of geographical location, the nature of social networks and the strength of private redistribution systems, thus enabling an easier access to means of existence. The results and recommendations are further discussed in the paper.
Keywords: Egypt; Greater Cairo; housing rehabilitation; informal settlements; livelihood; living conditions; low-income housing; modes of economic integration; occupancy rates; poor people; public housing; redistribution; squatter settlements

Is Environmental Management Really More Collaborative? A Comparative Analysis of Putative ‘Paradigm Shifts’ in Europe, Australia, and the United States - Benson, David; Jordan, Andrew; Smith, Laurence (Environment and Planning A, 2013)
It is a truism that environmental management has experienced a significant change in the locus of governing, in which centralised forms of steering have been gradually replaced by more collaborative management approaches organised at the ecosystem scale. Whereas much research capital has been expended on informing their design and promoting their uptake, surprisingly little systematic comparative empirical research exists on the precise nature and extent of what is often described as a ‘paradigm shift’ in governing. We address this gap by examining how one issue often deemed to require deeper ‘collaboration’, namely, catchment management, has been addressed in three comparable federal political systems: the European Union; the USA; and Australia. On the basis of a fresh and more comparable account of the forms and modalities of collaboration, we reveal that, although collaboration has undoubtedly grown in recent decades, its depth and extent remains highly variable both across and within the three cases. We also examine what these subtly different geographical ‘contours of collaboration’ imply for future research and practice.
Keywords: catchment management; central control; collaboration; environmental science; federalism; governance; neoliberalism; paradigm shift

Rudderless in a Sea of Yellow: The European Political Economy Impasse for Renewable Transport Energy - Harvey, Mark; Pilgrim, Sarah (New Political Economy, 2013)
Faced with the twin challenges of anthropogenic climate change and ‘peak oil’, the need for an urgent and radical transformation of transport energy has been widely recognised. Adopting a neo-Polanyian economic sociology approach, this article asks what conditions European governance capacity to respond to these challenges, at either national or regional levels, using biofuels as a case study. It asks if the complexity of its political institutions, and the heterogeneity of interests and economic organisations, present ‘the biggest obstacle of all’ (Cohen 2007) to reduce fossil fuel dependency. By examining the European Commission level and comparing five countries, evidence is produced for a political failure in terms of continued fossil fuel dependency. Incumbent interests in the agricultural sector and a distinctively European legacy of a transport fleet dependent on fossil diesel, have led to a marriage of convenience between rapeseed farmers and vehicle manufacturers. As a consequence, rather than escaping from the path dependency on fossil fuels (Unruh 2000), Europe has gone down a cul-de-sac of rapeseed biodiesel inherently limited in scope, and with the low levels of greenhouse gas emissions savings. Ironically this outcome is in part an unintended consequence of opposition to biofuels from environmentalist groups and politics.
Keywords: agriculture; biodiesel fuels; biofuels; biomass energy research; climate change; climate change research; economics; peak oil; politically instituted markets; rapeseed

The Commodification of Pollution and a Preemptive Double Movement in Environmental Governance: The Case of Water Quality Trading - Mariola, Matt J. (Organization & Environment, 2011)
The management of environmental pollution has traditionally been accomplished via the regulatory power of the state, but more recently the rise of a new, market-based form of governance has been observed. This article examines the sector of water quality trading, in which caps are placed on surface water pollution and polluters can purchase “offset credits” from farms or other polluters who are under their cap. Using a content analysis of program case studies and federal and state trading rules, the author analyzes this emergent form of environmental governance using an expanded Polanyian framework that he terms the preemptive double movement. Instead of the state reacting to the dangers of a new market form after the fact, here the state uses its existing authority to constrain the market so that further environmental damage does not result. The author describes eight specific regulatory mechanisms that illustrate this preemptive double movement at work.
Keywords: Polanyi; business & the environment; commodification; double movement; ecological impact; nutrient trading; pollution; water quality management; water quality trading

O diferencial do empreendedorismo solidário - Gaiger, Luiz Inácio; da Silva Corrêa, Andressa (The uniqueness of solidarity entrepreneurship., 2011)
The article aims to bring evidence that the solidarity economic undertakings, based on voluntary association, productive cooperation and self-management, employ a unique rationality, different from the capitalistic one. Classical authors such as Schumpeter, Polanyi and Weber, besides some scholars dedicated to the solidarity economy or to micro-entrepreneurship, such as Laville, Portela and Hespanha, give us a theoretical framework, which is used to review the concept of entrepreneurship and to discuss the findings of some empirical investigations, particularly regarding solidarity micro-enterprises. The data base under analysis is provided by the national mapping of the solidarity economy in Brazil and by a qualitative study about small solidarity-based economic experiences, which focused on the relevance of self-management and cooperation, as well as of efficiency and sustainability. Despite their weaknesses and limitations, these experiences reveal the existence of a particular associative kind of entrepreneurship, guided simultaneously by economic and social objectives. This provides convincing empirical arguments for the adoption of a specific approach on entrepreneurship in the context of the solidarity economy and, under certain aspects, in the broader context of small enterprises. (English)
Keywords: SCHUMPETER, Joseph Alois, 1883-1950; WEBER, Max, 1864-1920; associations, institutions - management; associativism; associativismo; economic rationality; entrepreneurship; micro-entrepreneurship; microempreendedorismo; racionalidade econômica; solidarity; solidarity economy; sustainability; works councils

Who decides what is fair in fair trade? The agri-environmental governance of standards, access, and price - Bacon, Christopher M. (The Journal of Peasant Studies, 2010)
The agri-environmental governance of value chains can favour a Polanyian double movement seeking social protection and control over price setting markets or it can advance a neoliberal logic that strives to overcome the few remaining civic and ecologic obstacles to full market dominance. Coupled with a typology that contrasts corporate social responsibility and social economy Fair Trade models, this theoretical framework elucidates positions in the current policy debates about the minimum coffee price standard. Many Southern smallholders consider Fair Trade's standards, which for coffee include direct market accesses for smallholder cooperatives, minimum prices, and environmental criteria, among the best deals available. The smallholder empowerment benefits are often better than competing eco-labels. However, this study finds that Fair Trade minimum prices lost 41 percent of their real value from 1988 to 2008. Despite objections from several ‘market driven’ firms and national labelling initiatives, smallholders' collective advocacy and this research contributed to the Fairtrade Labelling Organisations International's (FLO) decision to mandate a 7–11 percent minimum price increase. The price debates demonstrate that Fair Trade governance is neither purely neoliberal nor social movement led – it is a highly contested socially embedded practice. Voices without votes, North–South inequalities, and dwindling prices paid to its stated protagonists indicate the need for governance reform, cost of living price adjustments, and additional investment in the innovative alternative trade and hybrid models.
Keywords: double movement; eco-labels; environmental and agricultural governance; environmental science; environmental studies; fair trade; peasant studies; standards; sustainability

Karl Polanyi, the New Deal and the Green New Deal - Dale, Gareth (Environmental Values, 2021)
In this paper, I present an analysis of those aspects of Karl Polanyi's social and political thought that relate to environmentalism and 'green' politics today. I discuss whether or not he prefigured the degrowth movement, before focusing on his understanding of the New Deal (1933-1939). At the time of writing, the prospect appears likely of a return, at a global scale, of economic slump, mass unemployment and ecological crisis, the background conditions to which Franklin D. Roosevelt's New Deal was responding on the national scale. The paper concludes by drawing lessons from this comparison for possible Green New Deals.
Keywords: Green New Deal; Karl Polanyi; New Deal; degrowth; embeddedness

On the Nature of the Countermovement: A Response to Stuart et al.’s ‘Climate Change and the Polanyian Countermovement: Carbon Markets or Degrowth?’ - Carton, Wim (New Political Economy, 2020)
In a recent article for this journal, Stuart, D., Gunderson, R., and Petersen, B. [(2017). Climate change and the Polanyian counter-movement: carbon markets or degrowth? New political economy, 1–14. doi:10.1080/13563467.2017.1417364] discuss solutions to climate change in terms of Karl Polanyi’s concept of the double movement. They set up their argument as a critique of my own article on the topic to make the point that carbon markets do not constitute a genuine form of such countermovement. I’m sympathetic to the critique of carbon markets that the authors present, as well as their discussion of degrowth, which mirrors a by now extensive literature demonstrating the pitfalls respectively the necessity of these diametrically opposed approaches to the current socioecological crisis. However, in setting up their case the authors provide an overly optimistic reading of Polanyi that I believe misses a crucial part of his argument, a reading that at least partly explains our differences in opinion. This commentary offers a friendly critique of Stuart et al.’s use of Polanyi and clarifies the argument in my previous text that the authors take issue with.
Keywords: Polanyi; carbon markets; climate change; commodification; countermovement